Pengaruh Meminta dan Memberi Maaf terhadap Kesehatan Jiwa dan Raga - Zul Efendi; Ananda Farhan; Erlina Erlina (Jurnal Budi Pekerti Agama Islam, 2026)
Forgiveness, both in the form of asking for and granting forgiveness, plays an important role in maintaining individuals’ psychological and physical well-being. In social life, individuals are inseparable from conflicts that can trigger negative emotions such as anger, hatred, and disappointment, which, if not properly managed, may affect mental and physical health. This study aims to analyze the effect of asking for and granting forgiveness on mental and physical health. The research employs a qualitative approach using a literature review method by examining various relevant scientific sources related to forgiveness and health. The findings indicate that forgiveness contributes significantly to reducing negative emotions, lowering stress levels, and improving psychological well-being. In addition, forgiveness also has a positive impact on physical health, particularly in stabilizing physiological conditions influenced by stress responses. Individuals who are able to forgive tend to have better emotional control, healthier social relationships, and an overall improved quality of life. Therefore, forgiveness is not only a moral or social act but also an important psychological mechanism in maintaining holistic health.